2013
DOI: 10.1371/journal.pone.0064946
|View full text |Cite
|
Sign up to set email alerts
|

RNAi Screening in Primary Human Hepatocytes of Genes Implicated in Genome-Wide Association Studies for Roles in Type 2 Diabetes Identifies Roles for CAMK1D and CDKAL1, among Others, in Hepatic Glucose Regulation

Abstract: Genome-wide association (GWA) studies have described a large number of new candidate genes that contribute to of Type 2 Diabetes (T2D). In some cases, small clusters of genes are implicated, rather than a single gene, and in all cases, the genetic contribution is not defined through the effects on a specific organ, such as the pancreas or liver. There is a significant need to develop and use human cell-based models to examine the effects these genes may have on glucose regulation. We describe the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…This process may be an attempt by the adipose tissue to try and restrict lipid accumulation and, thus, restoring functionality in the tissue. CAMK1D is currently not well characterized in terms of biological function, however, as well as being involved in inflammatory signaling, evidence from the liver suggests that it is important for glucose metabolism (38). The impact of increased of CAMK1D and IL-33 expression on adipocytes warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This process may be an attempt by the adipose tissue to try and restrict lipid accumulation and, thus, restoring functionality in the tissue. CAMK1D is currently not well characterized in terms of biological function, however, as well as being involved in inflammatory signaling, evidence from the liver suggests that it is important for glucose metabolism (38). The impact of increased of CAMK1D and IL-33 expression on adipocytes warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…CAMk1D has been reported to be associated in GWAS meta-analysis studies with type II Diabetes (Zeggini et al, 2008) and was later shown to reduce glucose response , possibly due to an effect on the localization of a mediator of both gluconeogenesis and glycolysis (Haney et al, 2013). This raises the question about the effect of metabolic process in Ndel1 measures and whether they converge to impact on SCZ pathophysiology or whether Ndel1 would be only a biomarker of these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Camk1d is member of the calcium/calmodulin-dependent protein kinase 1 gene family that plays role in granulocyte respiratory burst, phagocytosis, adhesion and migration [ 35 ]. It is also known to activate CREB-mediated transcriptional activation [ 36 ] and may play a role in regulating hepatocyte glycolysis and gluconeogenesis independent of insulin signaling [ 37 ]. Of important relevance to this project, variants in Camk1d have replicated association with Type II diabetes [ 24 26 ] and a recent study also found association of this gene to hypertension [ 38 ].…”
Section: Discussionmentioning
confidence: 99%